2017
DOI: 10.6018/analesps.33.3.269211
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mediation of Loneliness and Negative Emotions in the Relationship between Adolescents’ Social Anxiety and Depressive Symptoms

Abstract: Título: Mediación múltiple de la soledad y las afecta negativas en la relación entre la ansiedad social de los adolescentes y los síntomas depresivos. Resumen: La presente investigación tiene como objetivo investigar la mediación múltiple de la soledad y de los afectos negativos en la relación entre la ansiedad social y los síntomas depresivos de los adolescentes. Los participantes del estudio, seleccionados mediante muestreo por conveniencia, fueron un total de 263 estudiantes, incluyendo a 155 mujeres (59%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
14
0
1
Order By: Relevance
“…A study in China at the peak of the pandemic showed that home quarantine was part of the psychosocial stressors that were significantly associated with the development of anxiety and depression ( 8 ). Several studies have indicated that lonely individuals are more likely to have anxiety and depression as they do not have adequate social support ( 37 , 39 , 61 ). People have been experiencing emotional exhaustion during this pandemic period and have been unable to unleash their emotions due to the isolation faced in the lockdown ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in China at the peak of the pandemic showed that home quarantine was part of the psychosocial stressors that were significantly associated with the development of anxiety and depression ( 8 ). Several studies have indicated that lonely individuals are more likely to have anxiety and depression as they do not have adequate social support ( 37 , 39 , 61 ). People have been experiencing emotional exhaustion during this pandemic period and have been unable to unleash their emotions due to the isolation faced in the lockdown ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative affect that individuals experience are critical in predicting mental disorders (Leue & Langei, 2011). It is known that individuals mostly experience negative affects during depression (Baytemir & Yıldız, 2017) For instance, some clinical studies showed that ineffective and dysfunctional emotion regulation was a significant dimension when disorders such as depression and anxiety emerge and progress (Barlow, Allen, & Choate, 2004;Duy & Yıldız, 2017;Mennin, 2006). Based on this, it can be said that an individual's effective emotion regulation against intense negative affects may return the course of depression from negative to positive.…”
Section: Introductionmentioning
confidence: 99%
“…PA and NA are not opposites states and can occur independently and simultaneously [51] . Individuals who are lonelier compared with less lonely counterparts have been shown to report lower positive affect (e.g., interested) and more negative affect (e.g., upset; [52][53][54] ). Indeed, within the current cognition model of loneliness [48] , those who are lonelier compared with those who are less lonely, also report less positive affect [55] and fewer prosocial behaviours.…”
Section: Factors Contributing To Lonelinessmentioning
confidence: 99%